2018
DOI: 10.5039/agraria.v13i2a5517
|View full text |Cite
|
Sign up to set email alerts
|

Minerais ferruginosos e fertilidade natural de solos magnéticos do Vale do Jequitinhonha, Minas Gerais, Brasil

Abstract: RESUMO:Este estudo teve como objetivo caracterizar as naturezas química e mineralógica de solos derivados de materiais de origem básicos e ácidos do Vale do Jequitinhonha, Minas Gerais, Brasil, com foco na ocorrência de minerais magnéticos e suas relações com a fertilidade natural. ABSTRACT: This study aimed at characterizing the chemical and mineralogical nature of soils derived from basic and acidic bedrocks from the Jequitinhonha Valley, Minas Gerais State, Brazil, focusing on the occurrence of magnetic min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Rhodic Oxisols exhibit strong magnetic attraction due to high contents of ferrimagnetic Fe oxides (maghemite and magnetite) (Costa et al, 1999(Costa et al, , 2014Camêlo et al, 2018;Poggere et al, 2018). These minerals have often been used in studies on pedogenesis (Silva et al, 2017;Camêlo et al, 2018) for stratification of environments (Ramos et al, 2017) and soil fertility (Costa et al, 2018) in Brazil and elsewhere in the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhodic Oxisols exhibit strong magnetic attraction due to high contents of ferrimagnetic Fe oxides (maghemite and magnetite) (Costa et al, 1999(Costa et al, , 2014Camêlo et al, 2018;Poggere et al, 2018). These minerals have often been used in studies on pedogenesis (Silva et al, 2017;Camêlo et al, 2018) for stratification of environments (Ramos et al, 2017) and soil fertility (Costa et al, 2018) in Brazil and elsewhere in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several authors have reported on magnetite predominance in the coarse fractions (sand and silt) and maghemite in the clay fraction (Costa et al, 1999;Carvalho Filho et al, 2015;Camêlo et al, 2018;Poggere et al, 2018) of Fe-rich Rhodic Oxisols in Brazil. However, it is known that both minerals can display distinct soil size fractions or occur in all of them (Causevic et al, 2004;Maxbauer et al, 2016;Silva et al, 2017;Costa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%